Studying the Implementation of Finite Element Models in the Orthogonal Cutting Processes with Uncoated Tool and TiN, TiCN and Al2O3 Coated Tool - Nguyen, Kien Trung; Truong, Hoanh Son (Old Journal, 2018)
The metal machining is the most popular process used in the machinery part manufacturing. Therefore, machining process needs to be controlled by properly selecting of cutting condition, tool materials and coating to obtain the best machining time, good surface finish and low machining cost at the same time. To understand the effects of various cutting condition, tool and coating materials, it is useful to simulate the machining process using finite element techniques. This paper presents the preliminary investigation on the implementation of two dimensional finite element modeling (FEM) with two approaches, Lagrangian mesh description and Arbitrary Eulerian-Lagrangian (ALE) mesh description, to simulate the stress and cutting temperature in the orthogonal cutting processes. The influence of various tool and coating materials (TiN, TiCN and Al2O3 carbide coated tool, Polycrystalline Diamond - PCD) is also studied in comparison with uncoated tool. Titanium alloy Ti-6Al-4V and AISI 1045 steel is selected as work materials in these FEM models. The results show that the FEM model with ALE approach are adequate to simulate the stress and temperature distribution with a high accuracy while the FEM model with Lagrangian approach is capable in simulate chip formation.